En coup de sabre morphea: An uncommon condition in Africa - Lehlohonolo Makhakhe; Ncoza Dlova; Annette Smith; Michelle du Preez (PAGEPress Publications, 2022)
The term en coup de sabre morphea refers to a lesion of linear morphea typically located in the frontoparietal scalp and/or the paramedian forehead, often resembling a strike with a sword. In literature, en coup de sabre morphea and en coup de sabre scleroderma are terms used interchangeably and synonymously. Due to the rarity of this condition, treatment is largely based on case report series, leaving much room for speculation in terms of drugs of choice, duration of treatment and dosages. Although typically leaving behind notable and often permanent skin pigmentary changes and indentation of the affected areas, this condition usually remits spontaneously, even in the absence of active form of treatment. The disease severity and prognosis vary according to the subtype: circumscribed morphea has a generally more benign course when compared with linear scleroderma and generalised morphea.